Development of the Education System Being Superior Madrasahs - Qomarudin, Muslih; Puspitasari, Tuti; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
Development of a superior madrasah education system, including a graduate system, curriculum, education staff, facilities and infrastructure, lesson plan management, financing, and assessment. Building discipline and work ethic for madrasa teaching and education staff, building cooperation within the madrasah environment, and developing strategies for teaching and learning activities are all strategies for developing superior madrasas. The superior madrasa development strategy is supported by the fact that this madrasa pays attention to madrasa facilities and infrastructure, adequate learning resources, and teachers at MIN 4 Way Kanan Regency. The impediment to superior madrasa development strategy is the likelihood of it occurring in madrasas, namely inadequate facilities and infrastructure, more learning resources, and fewer teachers. Implications of research where the feel is the Madrasa itself because it can improve or discover how this madrasa can lead to a superior madrasa with various systems and strategies.